The book swap [large type] - Bickers, Tessa (Thorndike Press Large Print softcover romance and women's fiction., 2024)
Still reeling from a recent tragedy, Erin Connolly knows she needs to start living, but has no idea how. When she accidentally donates her favorite book--a heavily annotated copy of To Kill a Mockingbird containing a memento she can't be without--to a local little community library, she's devastated. But then the book turns up a week later, back in the library with fresh notes in the margins, along with an invitation in a copy of Great Expectations to meet her newfound pen pal. A life-changing conversation, written only in the margins of beloved classic books, begins between Erin and her Mystery Man. Following each other through the pages of their favorite novels as the book exchange continues, they both begin to open up, falling into a friendship...and maybe something more. But Erin and her pen pal have a shared history that neither of them has guessed. Faced with painful reminders of the past--and the one person she swore never to forgive--Erin finds herself at a crossroads. One that could change her life forever.